First Successful Hindcasts of the 2016 Disruption of the Stratospheric Quasi‐biennial Oscillation. Issue 3 (2nd February 2018) - Watanabe, S.; Hamilton, K.; Osprey, S.; Kawatani, Y.; Nishimoto, E.
Abstract: In early 2016 the quasi‐biennial oscillation in tropical stratospheric winds was disrupted by an anomalous easterly jet centered at 40 hPa, a development that was completely missed by all operational extended range weather forecast systems. This event and its predictability are investigated through 40 day ensemble hindcasts using a global model notable for its sophisticated representation of the upper atmosphere. Integrations starting at different times throughout January 2016—just before and during the initial development of the easterly jet—were performed. All integrations simulated the unusual developments in the stratospheric mean wind, despite considerable differences in other aspects of the flow evolution among the ensemble members, notably in the evolution of the winter polar vortex and the day‐to‐day variations in extratropical Rossby waves. Key to prediction of this event is simulating the slowly evolving mean winds in the winter subtropics that provide a waveguide for Rossby waves propagating from the winter hemisphere. Plain Language Summary: In early 2016 the regular winds high up in the tropical atmosphere were disturbed in a way not seen in over 60 years of observations. The usual regularity of the year‐to‐year changes in these winds contributes to skillful long range weather forecasts worldwide, so when weather centers failed to pick up this event, predictions of seasonal weather were affected. This study reports a successful retrospective forecast of the 2016 disruption event using a global climate model notable for its detailed representation of the upper atmosphere and provides a benchmark for future forecast models. It has been found that dramatic changes to the high‐latitude winds in the upper atmosphere had little influence on the development of the tropical anomaly, but rather the distribution of prevailing winds closer to the tropics was crucially important. Key Points: The unprecedented disruption in 2016 of the QBO was successfully captured in a series of 40 day ensemble hindcasts The QBO disruption is caused by the interaction of Rossby waves of extratropical origin with the equatorial mean flow The individual ensemble members displayed quite similar equatorial mean wind evolution despite large differences in the extratropics